2019
DOI: 10.21873/invivo.11670
|View full text |Cite
|
Sign up to set email alerts
|

EBV LMP1 in Gingival Epithelium Potentially Contributes to Human Chronic Periodontitis via Inducible IL8 Production

Abstract: Background/Aim: Human chronic periodontitis is a major health problem. Although some oral bacteria have been reported to be putative pathogens, Epstein-Barr virus (EBV) is reported to be associated with the progression of periodontitis. However, the role of EBV in the aetiology of periodontitis is unknown. Therefore, we investigated periodontal pathogenesis of EBV to confirm whether EBVencoded latent membrane protein 1 (LMP1) induces Interleukin-8 (IL8) production in human gingival cells. Materials and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 45 publications
1
13
0
2
Order By: Relevance
“…Another study indicated the mechanism of EBV infection, which correlates with the severity of chronic periodontitis. EBV-encoded latent membrane protein 1 (LMP1) induces interleukin-2 (IL-8) production in human gingival cells [ 57 , 58 ], and the presence of IL-8 as well as proinflammatory cytokine levels in the gingival crevicular fluid are closely associated with the severity of inflammation and periodontal destruction [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated the mechanism of EBV infection, which correlates with the severity of chronic periodontitis. EBV-encoded latent membrane protein 1 (LMP1) induces interleukin-2 (IL-8) production in human gingival cells [ 57 , 58 ], and the presence of IL-8 as well as proinflammatory cytokine levels in the gingival crevicular fluid are closely associated with the severity of inflammation and periodontal destruction [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies are thus far available that describe de novo etiological significance for the onset or progression of chronic periodontitis with latent EBV infection in the periodontium. We therefore introduce herein some progress in understanding EBV-related periodontal etiology from Doglio's group and ours [17,48,49].…”
Section: Etiological Significances Of Ebv Infection In the Periodontiummentioning
confidence: 99%
“…To further investigate mechanisms pertaining to pathogenesis of EBV latently infected periodontium, we recently examined potential periodontal pathogenesis associated with LMP1 [49]. C-terminal activating region (CATR) domains of LMP1 bind to TNF receptor-associated factor and TNF receptor-associated death domain protein.…”
Section: Etiological Significances Of Ebv Infection In the Periodontiummentioning
confidence: 99%
“…Immunoblot assay. The experimental procedures for immunoprecipitation and immunoblotting were performed according to previously published protocols (22,23). Briefly, cells were harvested with lysis buffer [25 mM HEPES-NaOH (pH 7.9), 150 mM NaCl, 1.5 mM MgCl 2 , 0.2 mM EDTA, 0.3% NP-40, 1 mM dithiothreitol, 0.5 mM phenylmethylsulfonyl fluoride], the proteins were separated by SDS-PAGE and transferred to a polyvinylidene fluoride membrane (EMD Millipore Corporation, Billerica, MA, USA).…”
Section: Saliva Collectionmentioning
confidence: 99%